Parental mediation practices of children's internet use in Kajang, Selangor / Nasha Farena Rosli - Rosli, Nasha Farena (2019)
Technology is a necessity for society today. In addition, the world is becoming more sophisticated and rapid changes require dependence on technological literacy. The role of parents is increasingly being challenged by children exposed to the cyber world from an early age. The role of parents in mediating children in relationships is crucial in protecting children from the dangers of cyber threats. The main of this study is to examine the relationship between parental mediation practices of children's internet use and cyber parenting knowledge in Kajang, Selangor. The core study's objectives are to examine the relationship between cyber parenting knowledge and parental mediation practices of children's internet use in Kajang, Selangor, to determine the relationship between children's internet addiction and parental mediation practices of children's internet use, and to determine the most contributing factor towards parental practices. The research design of this study has adopted a cross-sectional and correlational approach. The quantitative method has been applied and a total (N=398) set of questionnaires had been distributed to Kajang, Selangor residents specifically parents who have at least one child. The Statistical Package for Social Science (SPSS) Version 22.0 was used in the study for data analysis. Based on the findings, it was found that there was a relationship (r=0.063, p<0.05) between cyber parenting knowledge and parental mediation practices of children's internet use whereas, there was no relationship (r=0.000, p (0.999) >0.05) between children's internet addiction and parental mediation practices of children's internet use. Finally, the main contributing factor to this study is parenting cyber knowledge among residents in Kajang, Selangor. The results of this study lead to several recommendations provided to society, and the Malaysian Government as a way to become more concerned about society's issues. Lastly, it has also been suggested that future research enlarges new comprehensive strategies in the context of parental mediation practices.